2023
DOI: 10.5603/gp.a2023.0036
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic potential of microRNAs Mi 517 and Mi 526 as biomarkers in the detection of hypertension and preeclampsia in the first trimester

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited.Articles in "Ginekologia Polska" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Circulating levels of miR-942 were lower at midpregnancy (12-20 weeks' gestation) in women with preeclampsia than in the control A study by Luque et al [153] indicated that the assessment of maternal serum microR-NAs at the end of the first trimester of pregnancy does not appear to have any predictive value for early preeclampsia. Other studies, however, have strongly supported the need for more detailed exploration of microRNAs in the maternal circulation since they represent potential biomarkers for pregnancy-related complications [146,152,158,159]. There is a need to consider that increased placental dysfunction may stimulate the gradual release of placental mediators, including miRNAs, into the maternal circulation, leading to further diffuse maternal vascular damage and increased differential profiles of circulating miRNAs only at later stages of gestation.…”
Section: Mirnas and Prediction Of Preeclampsiamentioning
confidence: 99%
“…Circulating levels of miR-942 were lower at midpregnancy (12-20 weeks' gestation) in women with preeclampsia than in the control A study by Luque et al [153] indicated that the assessment of maternal serum microR-NAs at the end of the first trimester of pregnancy does not appear to have any predictive value for early preeclampsia. Other studies, however, have strongly supported the need for more detailed exploration of microRNAs in the maternal circulation since they represent potential biomarkers for pregnancy-related complications [146,152,158,159]. There is a need to consider that increased placental dysfunction may stimulate the gradual release of placental mediators, including miRNAs, into the maternal circulation, leading to further diffuse maternal vascular damage and increased differential profiles of circulating miRNAs only at later stages of gestation.…”
Section: Mirnas and Prediction Of Preeclampsiamentioning
confidence: 99%